Bahasa Indonesia Bahasa Inggris: Bahasa Inggris - Maurin Devina Juwita; Anggun Lestari; Enggar Agmasari (Ecobankers : Journal of Economy and Banking, 2026)
Production constitutes one of the fundamental activities within an economic system, playing a pivotal role in fulfilling human needs and stimulating economic growth. In contemporary economic practice, production activities are frequently oriented toward achieving efficiency and maximizing profit, thereby potentially neglecting moral, social, and environmental considerations. This study aims to analyze the concept of production from the perspective of Islamic economics, which conceptualizes economic efficiency and moral responsibility as an integrated and inseparable unity. The research employs a library-based method by examining relevant literature, including scholarly books, peer-reviewed journal articles, and other academic sources addressing Islamic economics and production theory. The findings indicate that production in Islamic economics not only emphasizes the optimization of factors of production and the enhancement of output, but also prioritizes the principles of halal (lawful) production, justice, public welfare (maslahah), as well as social and environmental responsibility. Producers are regarded as trustees (amanah) who bear the obligation to generate goods and services that are beneficial and aligned with Islamic values. Accordingly, Islamic economics offers a balanced production framework that integrates economic objectives with moral values, thereby holding the potential to foster a more equitable and sustainable system of production   Keywords: Production; Islamic Economics; Economic Efficiency; Moral Responsibility